2017
DOI: 10.1016/j.jaci.2016.12.597
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions to Maintain Penicillin Allergy Label Removal As Part of an Inpatient Penicillin Allergy Testing Protocol

Abstract: Abstracts AB183SUNDAY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…9 In fact, it is estimated that 36% to 49% of patients with negative penicillin testing results may have a persistence or redocumentation of their allergy despite proven negative testing results. [147][148][149] Current evidence reveals that an interactive and electronically accessible drug allergy box in a medical record that is regularly reconciled improves the management of patients labeled with drug allergies. In 1 study, the electronic medical record was used proactively to identify patients for testing, which was then performed in the inpatient unit by a trained pharmacist.…”
Section: Antibiotic Stewardship Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In fact, it is estimated that 36% to 49% of patients with negative penicillin testing results may have a persistence or redocumentation of their allergy despite proven negative testing results. [147][148][149] Current evidence reveals that an interactive and electronically accessible drug allergy box in a medical record that is regularly reconciled improves the management of patients labeled with drug allergies. In 1 study, the electronic medical record was used proactively to identify patients for testing, which was then performed in the inpatient unit by a trained pharmacist.…”
Section: Antibiotic Stewardship Programsmentioning
confidence: 99%
“…150 Researchers in another small pilot study prevented redocumentation with several interventions, including an electronic alert notifying providers when a penicillin allergy is added back for a patient with documented negative testing results. 148 Targeting prospective antibiotic allergy management in adults has led to a positive impact on antibiotic use and appropriateness. 151 periods among an internal medicine service and showed that inpatient skin testing to β-lactam drugs directed by an allergist and the use of previously adopted, computerized guidelines resulted in an increase in penicillin and cephalosporin use.…”
Section: Antibiotic Stewardship Programsmentioning
confidence: 99%
“…It is important to input the date and results of PST into the patient’s problem list and insert a placeholder in the allergy section of the EMR with the same information in an effort to prevent relabeling of the penicillin allergy. Some institutions also have the capability to add in an electronic alert that will appear if a provider is entering a penicillin allergy in the allergy section of a patient’s chart who previously had a negative PST [40,41]. In order to further assist in the prevention of penicillin allergy relabeling, PST programs need to take a multi-faceted approach that involves communication to patient and their families, providers within and outside the healthcare network, and community pharmacies.…”
Section: Penicillin Allergy Documentationmentioning
confidence: 99%
“…If this step is omitted and a patient presents to the pharmacy with a prescription for a beta-lactam antibiotic with a penicillin allergy listed in the patient profile, a potentially unnecessary phone call will be made by the pharmacist to the provider to clarify the beta-lactam prescription or recommend an alternative antibiotic. Some PST programs also perform a post-test telephone call by a pharmacist to other healthcare professionals to reinforce the results of PST [41].…”
Section: Penicillin Allergy Documentationmentioning
confidence: 99%
“…Pharmacy-led counselling and provision of a wallet card detailing the results and implications of testing have been successfully used in some areas. 85 Whilst a consensus was not sought on this topic, the authors recommend that, as a minimum, written evidence of testing is provided to the patient and their primary care physician, and the electronic hospital record is updated accordingly. A wallet card that is standardised across geographical regions and becomes embedded in local practice might help prevent relabelling.…”
Section: Dissemination Of Results After Testingmentioning
confidence: 99%